SMES DEVELOPMENT STRATEGY OF FOOTWEAR BUSINESS - Ibrahim , Syufriadi; Ridho Nurrochmat , Dodik; Maulana , Agus (LPPM Universitas Terbuka, 2019)
The main objective of this research is to analyze the strategy of developing the footwear business. Case studies were carried out at CV Hikmah Shoes Bogor. The initial analysis was carried out by identifying the business of the ongoing CV Hikmah Shoe model and analyzing the external and internal scope to identify problems that occurred in the company. The descriptive method used to identify CV Hikmah Shoes Bogor using, Internal Factor Matrix (IFE) and External Evaluation Factor (EFE) used to analyze internal and external factors at CV Hikmah Shoesr. SWOT matrix selected to determine the strategy to be implemented and Quantitative Strategy Planning Matrix (QSPM) is used as a process to determine strategic priorities for the company. The results of the SWOT Matrix in this study produced six alternative strategies that were chosen as development strategies at CV Hikmah Shoes, Bogor. results The best strategy taken in developing the footwear business is to maximize promotion and marketing using social media or e-commerce and to continue with the improvement business.